Pemberdayaan Masyarakat Desa Olak Keman Melalui Inisiasi Pengembangan Desa Wisata Berbasis Kearifan Lokal dan Potensi Sungai - Achmad, Erni; Hodijah, Siti; Hastuti, Dwi; Rachmad R, Muhammad; Eka Putra , Wirmi (Lembaga Pengabdian kepada Masyarakat Universitas Langlangbuana, 2025)
Olak Kemang Village, located along the Batanghari River in Jambi City, has strong potential to be developed as a tourism village based on Jambi Malay culture, river tourism, traditional culinary products, and local handicrafts such as Jambi batik. However, limited structured and participatory management has constrained the optimal utilization of these resources. This community service program aims to enhance community awareness and strengthen institutional capacity in managing local tourism potential sustainably. The objectives include providing training and education on tourism village development, establishing and mentoring a Tourism Awareness Group (Pokdarwis), identifying and documenting cultural, river, and culinary tourism potential, and developing digital promotional media. The program applied participatory methods consisting of training, mentoring, field observations, documentation, and digital media development involving community members and relevant stakeholders. The targeted outputs include the establishment of an active Pokdarwis, documented tourism potential mapping, a tourism promotional video with an approximate duration of three minutes, active tourism village social media accounts, and the publication of scientific or popular articles related to the program. This initiative is expected to initiate community-based tourism management, encourage sustainable local economic growth, and position Olak Kemang Village as a model tourism village based on local wisdom, thereby enhancing the tourism attractiveness of Jambi City